2013
DOI: 10.2310/8000.2013.130897
|View full text |Cite
|
Sign up to set email alerts
|

Emergency medicine procedural skills: what are residents missing?

Abstract: Objective: This study sought to establish the current state of procedural skills training in Canadian Royal College emergency medicine (EM) residencies. Methods: A national Web-based survey was administered to residents and program directors of all 13 Canadian-accredited Royal College EM residency programs. Program directors rated the importance and experience required for competence of 45 EM procedural skills. EM residents reported their experience and comfort in performing the same procedural skills. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…A participation bias among residents was also noted, with a stepwise decline in the response rate with advancing postgraduate year. This finding was similar to other surveys of EM residents 30 and may be due to increasing survey fatigue with advancing training or a focus on the final board certification exams, in the case of the final year residents. This may have acted to falsely inflate resident hours of reported simulation at institutions where simulation is offered to junior residents only.…”
Section: Limitationssupporting
confidence: 87%
“…A participation bias among residents was also noted, with a stepwise decline in the response rate with advancing postgraduate year. This finding was similar to other surveys of EM residents 30 and may be due to increasing survey fatigue with advancing training or a focus on the final board certification exams, in the case of the final year residents. This may have acted to falsely inflate resident hours of reported simulation at institutions where simulation is offered to junior residents only.…”
Section: Limitationssupporting
confidence: 87%
“… 7 , 12 14 This is especially concerning for a procedure-rich residency such as emergency medicine, anesthesia, and general surgery, where numerous procedures such as CVC are performed and can lead to complications. 15 , 16 The use of US has been shown to significantly decrease CVC complication risk, which may be further mitigated by improving procedural familiarity and competence through simulation education. 17 , 18 In fact, the Agency for Healthcare Research and Quality has identified US-guided central venous placement as one of the practices in which strong evidence supports its widespread implementation.…”
Section: Discussionmentioning
confidence: 99%
“…These include differences in training length, volume of patients in the emergency department (ED), trauma designation, geographic area, and amount of clinical time spent in the ED. Several studies have documented that neither pediatric EM (PEM) fellows nor EM residents have an opportunity to perform any of these critical procedures on children (Al-Eissa et al, 2008;Petrosoniak, Herold and Woolfrey, 2013). Furthermore, pediatric faculty who may be in charge of teaching and supervising fellows about these procedures are likely to also have limited to no experience performing these procedures as well (Mittiga et al, 2013b;Mittiga, FitzGerald and Kerrey, 2016;Nguyen and Craig, 2016;Burns and Uspal, 2017).…”
Section: Introductionmentioning
confidence: 99%